The computer supported cooperative work impact of the applicability shopping in the federal government – electronic trading sessions - Pithon, Antonio José Caulliraux; Martins, Magali da Rocha; Fernandes, José Luiz (Revista de Administração da UFSM, 2017)
This article aims to analyze the extent to which public procurement can be speeded up by introducing collaborative work techniques to consistently control information, eliminate unproductive tasks and unnecessary bureaucracy and, as a consequence, increase efficiency and The quality of the process. In order to prove the data, a case study was carried out in the purchasing section of a Federal Institution with the purpose of introducing the techniques of computer supported collaborative work (CSCW) through the workflow tool, In government purchases that practice the electronic bidding modality. The data collected and tested showed that the implementation of this tool will make the purchasing process of the Institution faster and more efficient, indicating that it is possible to break the paradigm of bureaucratic culture that permeates government procurement.